2017
DOI: 10.1177/1367493516686203
|View full text |Cite
|
Sign up to set email alerts
|

22q11 deletion syndrome: Parents’ and children’s experiences of educational and healthcare provision in the United Kingdom

Abstract: Objective: 22q11DS is a genetic syndrome, prevalence around 1:4000-1:6000 livebirths, with a complex array of associated features, impacting on healthcare and educational support. This study reports the perceptions of families and individuals with 22q11DS in relation to these needs.Design: Individuals and families of those with 22q11DS were approached though two national charities the Max Appeal and 22Crew. An initial observational survey design was used to gather views via questions probing access to healthca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(25 citation statements)
references
References 21 publications
2
23
0
Order By: Relevance
“…A common finding concerning the lack of empathy and knowledge around 22q11DS was reported amongst educators and health‐care professionals (Cohen et al, 2017; Goodwin & McCormack, 2017; Goodwin, McCormack, et al, 2017; Karas et al, 2014; Klingberg et al, 2010; Martin et al, 2012; Phillips et al, 2017), this exacerbated the frustration and left many parents feeling like they had to fight for the care and support that their child deserves (Cohen et al, 2017; Goodwin & Mccormack, 2017). As a result, many parents and caregivers expressed feeling hopeless and worried.…”
Section: Resultsmentioning
confidence: 95%
See 4 more Smart Citations
“…A common finding concerning the lack of empathy and knowledge around 22q11DS was reported amongst educators and health‐care professionals (Cohen et al, 2017; Goodwin & McCormack, 2017; Goodwin, McCormack, et al, 2017; Karas et al, 2014; Klingberg et al, 2010; Martin et al, 2012; Phillips et al, 2017), this exacerbated the frustration and left many parents feeling like they had to fight for the care and support that their child deserves (Cohen et al, 2017; Goodwin & Mccormack, 2017). As a result, many parents and caregivers expressed feeling hopeless and worried.…”
Section: Resultsmentioning
confidence: 95%
“…Across the included studies, many parents reported feelings of powerlessness and frustration as a result of having to wait years for a diagnosis for their child (Bales et al, 2010a; Cohen et al, 2017; Costain et al, 2012), which resulted in increased uncertainty about the child's future (Bales et al, 2010a; Cohen et al, 2017; Costain et al, 2012; Goodwin & Mccormack, 2017; Goodwin, McCormack, et al, 2017; Karas et al, 2014; Martin et al, 2012). They also described a sense of relief when a diagnosis was given, and perceived that early justification for the child's symptoms can help psychological and clinical aspects of the illness earlier on in life (Cohen et al, 2017; Costain et al, 2012; Goodwin, McCormack, et al, 2017; Martin et al, 2012). Parents have praised the health care they received: one mother spoke about a pediatrician making the right referral in the process of finding a diagnosis (Bales et al, 2010a); another spoke about improved interactions between medical specialists and caregivers and patients when the clinicians were aware of the diagnosis (Costain et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations